Religion and politics in Nigeria: the role of religious actors in government decision making, 1980-2009 - Anyia, Albert Ethasor (2013)
In this thesis, I examine the role of religion in Nigerian government decision-making from 1980 to 2009, providing a clear and concise account of the ways in which selected Nigerian religious actors, such as the Christian Association of Nigeria and the Nigeria Supreme Council for Islamic Affairs interacted with government policy actors on two key policy issues: membership of the Organisation of Islam Conference (OIC; international policy) and the adoption of Sharia law (domestic policy). Demographically, Nigeria is equally divided between Christians and Muslims and religious belief is widespread and has no clear boundaries within the country's domestic politics and international relations. Religion and politics mix freely. playing significant roles in the individual's political and social relationships at all levels of society. Nigeria claims to have a secular constitution, but religion has become increasingly important in the public sphere and this thesis is primarily concerned with the political influence of religious actors in the Nigerian government decision-making process. Emphasis is put on investigating organizational access by religious interest groups to policy makers and their influence over policy outcome within the political process. If said groups and policymakers share religious allegiance, are these allegiances reflected in policy outcome? i.e. when and how do specific religious actors seek to influence the political outcomes of government decision-making? The finding of this thesis suggests that religious groups have a significant role in government decision-making, especially in relation to the impact that superior Muslim religious actors have within the policy-making structure in Nigeria on both OIC policy, and on the three arms of government in Muslim-dominated Sharia states. This study argues that such influence probably enhanced and promoted favourable policy outcomes for religious interest groups, especially Muslim groups.